New Synthetic Methodology Toward Azaspiro-γ-Lactones by Oxidative C–H Spirocyclization - Sengoku, Tetsuya; Nagai, Yuichiro; Inuzuka, Toshiyasu; Yoda, Hidemi (Synlett, 2019)
A new synthetic methodology for azaspiro-γ-lactones is reported. The key C–H spirolactonization was accomplished by employing iodobenzene diacetate and potassium bromide to afford a variety of azaspiro-γ-lactones in high yields. The reaction was also applicable to the preparation of a bislactone derivative.
Keywords: C–H spirolactonization; hypervalent iodine; azaspiro-γ-lactone; spiroheterocyclic compound; N,O-spirocycle